Variations in Maternal Behavior in C57BL/6J Mice: Behavioral Comparisons between Adult Offspring of High and Low Pup-Licking Mothers - Pedersen, Cort; Vadlamudi, Sivaramprasad; Boccia, Maria; Moy, Sheryl (Frontiers in Psychiatry, 2011)
The amount of maternal licking received by newborn rats affects their adult stress reactivity and maternal behavior. Mouse studies in which litters were cross-fostered between strains that exhibit high vs. low amounts of maternal behavior also suggest that rearing conditions affect adult outcomes. The current study is the first to compare within a single mouse strain (C57BL/6J) behavioral responses between adult animals reared by mothers that exhibited frequencies of pup-licking (PL) at the high end and the low end of the normal distribution within the strain. Maternal behaviors were coded during 10-sec intervals every 3 min during five 1-h periods (2 light, 3 dark cycle) on postpartum days 2, 4, 6 and 8 in 36 unrelated C57BL/6J mothers. The distribution of mean frequencies/h for PL, still crouched nursing, hovering over pups, self-grooming and no contact with pups were determined. Offspring (6-12 wks of age) from the 8 mothers who exhibited the highest mean frequencies of PL and the 7 mothers who exhibited the lowest PL frequencies underwent the following tests over 3 consecutive wks: 1) elevated plus maze (EPM) and 1-h open field on 3 successive days, 2) 3-h open field with an acute stressor (IP saline injection) at the 1-h time point, and 3) acoustic startle and prepulse inhibition. Females reared by low PL mothers exhibited significantly more time in the closed arms of the EPM, less locomotion, center time and rearing during the first test in the open field, greater reactivity to an acute stressor, and reduced prepulse inhibition, an index of sensorimotor gating. Male offspring from low PL dams had reduced reactivity to an acute stressor, but no other altered performance in the behavioral tests. PL frequencies of C57BL/6J mothers appear to selectively alter behavior outcomes, primarily in female offspring.